ChinaŽs WTO entry and the reform of grain circulation system - Qiao, Yan; Söderlund, Leif (MTT, 2005)
There are several severe problems in China s grain circulation system. In this report grain refers to cereal crops (rice, wheat and corn), soybeans and tubers. For example, the government cannot bear the heavy financial burden caused by grain procurement, and on the other hand, there are cost savings of the farmers lack of protection. Reform of the system began in 1998 and it still continues. The goals of the reform are to ensure the security of China s food supplies and to increase farmers income. After China s entry into the WTO, the reform was faced with new opportunities and challenges. On the basis of a series of analyses, some policy suggestions were put forward in this paper: (1) to reduce the appropriation of financial funds for grain procurement gradually and offer farmers direct subsidies in a suitable way as soon as possible; (2) to define properly the functions and scale of the central grain storage in order to avoid distortion of the grain market and increasing of the fiscal burden; (3) to optimize the allocation of domestic support funds, and make full use of the green box policies; (4) to accelerate the reform of state-owned grain enterprises and strengthen their competitiveness in the market; (5) to strengthen farmers cooperation, promote the farmers rural cooperatives and enhance their market-bargaining ability. In the long run, in order to ensure the national food security, China must protect the overall grain production capability fundamentally, including strengthening the protection of arable land and water resources and enhancing the S&T ability in rural areas.
Keywords: Ma; Ys; Kiina; viljelymenetelmät; maataloustulo; WTO; Maailman kauppajärjestö; China; grain circulation; WTO; World Trade Organization; food security; farmers income; ruokaturva